Health and economic impact of subcutaneous allergen immunotherapy in patients with pollen-induced allergic rhinoconjunctivitis: real-word evidence from the Czech Republic - Turková, Barbora; Tužil, Jan; Pilnáčková, Barbora; Doležalová, Helena; Štrosová, Daniela; Petrů, Vít; Seberová, Ester; Doležal, Tomáš (Immunotherapy, 2022)
Background: The prevalence of allergic rhinoconjunctivitis (AR) has been increasing over the years, and allergen immunotherapy (AIT) remains the only disease-modifying treatment. However, cost-effectiveness data remain scarce. Methods: In this single-arm, noninterventional, prospective, multicenter study, we describe the effectiveness, safety and costs of subcutaneous AIT for pollen-induced allergic rhinoconjunctivitis. Results: Of 471 new AIT users, 317 completed three courses of treatment, and symptoms improved in 96%; no serious adverse reactions were reported. The cost of symptomatic medication decreased by 49% and the cost of unscheduled specialist visits decreased by 73%. Except for AIT administration, total healthcare costs decreased by 54% compared with the baseline pollen season without AIT. Conclusion: In clinical practice, subcutaneous AIT is an effective treatment generating savings on symptomatic medication and unscheduled consultations.
Keywords: subcutaneous; Allergens; alergie; lidé; economics; allergy; costs; pollen; Desensitization, Immunologic; rhinitis; Hypersensitivity; prospektivní studie; Prospective Studies; Czech Republic; Pollen; pyl; effectiveness; Česká republika; desenzibilizace imunologická; alergeny; immunotherapy; savings; rhinoconjunctivis; Humans